The positive impact of identity-affirming mental health treatment for neurodivergent individuals - Kroll, Elizabeth; Lederman, Megan; Kohlmeier, Jonathan; Kumar, Komal; Ballard, Jaime; Zant, Izabella; Fenkel, Caroline (Frontiers in Psychology, 2024)
Introduction: The medical and social definitions of neurodivergence have become a common topic of discussion over recent years, and the way that we define, measure and report on conditions within the neurodivergent umbrella is changing. The objective of this study was to analyze differences in mental health symptom presentation at intake and compare treatment outcomes among three groups: clients with an affirming neurodivergent diagnosis, clients without an affirming diagnosis, and neurotypical clients. Methods: Data were collected at intake and discharge. Clients self-reported neurodivergent identity, neurodivergent diagnoses, as well as severity of depression symptoms, anxiety symptoms and self-harm frequency. One-way multivariate analysis of variance tests were run to assess differences in mental health symptoms at intake and discharge based on neurodivergent identity and corresponding diagnosis. When MANOVAs indicated significant differences, follow-up univariate one-way ANOVAs were conducted for each dependent variable. Results: Neurodivergent clients reported significantly worse mental health symptoms at intake than neurotypical clients, regardless of diagnosis status. Additionally, clients who identified as neurodivergent but did not report an affirming medical diagnosis reported significantly worse mental health symptoms than those who did report an affirming medical diagnosis. By discharge from IOP treatment, no significant differences were found in symptom change scores between neurodivergent and neurotypical individuals, or neurodivergent individuals with an affirming diagnosis and those without. Discussion: These findings highlight the importance of acknowledging client identity as a key component of mental health treatment. The act of validating symptoms and experiences, allowing accommodations when requested, and exploring identity formation regardless of diagnosis, allowed all clients who identified as neurodivergent to benefit from treatment.